2019
DOI: 10.1177/0265659019869792
|View full text |Cite
|
Sign up to set email alerts
|

Teachers observing classroom communication: An application of the Communicating Supporting Classroom Observation Tool for children aged 4–7 years

Abstract: The nature of ‘Teacher talk’ is likely to have a considerable bearing on the child’s learning but measuring the communication environment in the classroom can present challenges. One tool which does this is the Communication Supporting Classroom Observation Tool (CSCOT). Initial use suggested that it was valid and reliably used by specialists (psychologists and speech and language therapists) and special educational needs coordinators (SENCOs). A key question is whether it can be used routinely by classroom te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 31 publications
(63 reference statements)
1
21
0
Order By: Relevance
“…A strength of the included studies is that a number of significant and positive outcomes were achieved by teacher-led interventions ( n = 15) and future studies should continue to explore effectiveness in natural contexts (Bleses et al, 2018). It is also essential that educators are willing and able to incorporate the evidence-based strategies into their practice (Dagenais et al, 2012; Law et al, 2019; Lindsay et al, 2012). Stoiber and Gettinger (2016) suggest that the gap between research and practice should decrease when practitioners can easily incorporate strategies into their normal routines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strength of the included studies is that a number of significant and positive outcomes were achieved by teacher-led interventions ( n = 15) and future studies should continue to explore effectiveness in natural contexts (Bleses et al, 2018). It is also essential that educators are willing and able to incorporate the evidence-based strategies into their practice (Dagenais et al, 2012; Law et al, 2019; Lindsay et al, 2012). Stoiber and Gettinger (2016) suggest that the gap between research and practice should decrease when practitioners can easily incorporate strategies into their normal routines.…”
Section: Discussionmentioning
confidence: 99%
“…Stoiber and Gettinger (2016) suggest that the gap between research and practice should decrease when practitioners can easily incorporate strategies into their normal routines. As noted by Law et al (2019) and Shiel et al (2012), increased curricula demands, along with a greater focus on preparation for standardised assessment in the primary classroom, may make the incorporation of language-supporting practices more challenging and an understanding of the social validity of interventions (Greenwood et al, 2020) is crucial. Of the included studies, Spencer et al (2015) considered this by way of teacher questionnaire and Goodson et al (2010) sought to understand the impact of the intervention on time allocated to other practices in the classroom, but consideration in other studies was absent, making this a key area for development in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention themes were informed by the Communication Supporting Classroom Observation Tool (CSCOT) (Dockrell et al, 2015), comprising classroom-based activities within three domains; language learning opportunities (LLO), language learning interactions (LLI), and language learning environments (LLE). LLE was only briefly discussed in the first session, since previous research has found greater awareness among teachers for this domain than for LLO and LLI (Dockrell et al, 2015; Law et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Discourse skills, critical for later achievement, are built on vocabulary and grammar but also from children’s ability to engage in conversational turns. There is a need to move beyond a focus on vocabulary and reducing the word gap in interventions ( 41 ) to provide opportunities for extended discourse, to enhance the classroom language learning environment ( 74 , 75 ), and to develop strategies and resources for their children at entry to nursery ( 76 ).…”
Section: Discussionmentioning
confidence: 99%